2007
DOI: 10.1109/tpds.2007.1013
|View full text |Cite
|
Sign up to set email alerts
|

Selfish Grids: Game-Theoretic Modeling and NAS/PSA Benchmark Evaluation

Abstract: Abstract-Selfish behaviors of individual machines in a Grid can potentially damage the performance of the system as a whole. However, scrutinizing the Grid by taking into account the noncooperativeness of machines is a largely unexplored research problem. In this paper, we first present a new hierarchical game-theoretic model of the Grid that matches well with the physical administrative structure in real-life situations. We then focus on the impact of selfishness in intrasite job execution mechanisms. Based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 45 publications
0
33
0
1
Order By: Relevance
“…Coping with peer abuses and selfishness: Various malicious behavior models should be investigated to secure P2P system applications. New mechanisms are needed to deal with intrusions, free riders, black mouths, collusions, and selfishness of peers [12], [14], [37].…”
Section: Conclusion and Further Workmentioning
confidence: 99%
“…Coping with peer abuses and selfishness: Various malicious behavior models should be investigated to secure P2P system applications. New mechanisms are needed to deal with intrusions, free riders, black mouths, collusions, and selfishness of peers [12], [14], [37].…”
Section: Conclusion and Further Workmentioning
confidence: 99%
“…Song et al (2005; considered risky and insecure conditions in online scheduling in grids caused by software vulnerability and distrusted resources. They applied a game-theoretical model introduced by Kwok et al (2007) for modeling resource owners selfish behavior in the hierarchical grid structure. A Space Time Genetic Algorithm (STGA) was implemented as the main mechanism of three risk-resilient meta-heuristics, named as risky, preemptive and replicated STG algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…Kwok et al (2007) presented a hierarchical grid model with three main levels: the global, the inter-site and the intra-site level. At the intra-site level, there is a federation of autonomous resources.…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Kwok et al [15] presented a hierarchical Grid computing model by taking machine selfishness into consideration and proposed a non-cooperative game theory based intrasite job execution mechanism. They found that the optimal selfish strategy significantly outperforms the Nash selfish strategy.…”
Section: Related Workmentioning
confidence: 99%